Heavy Metal and Nutritional Profiles of Sargassum crassifolium Flour from Tomini Bay - Renofandi A. Dien; Faiza A. Dali; Shindy Hamidah Manteu (International Journal of Multidisciplinary Sciences and Arts, 2026)
Sargassum crassifolium is a nutrient-dense brown macroalga with significant potential as a functional food ingredient, yet its utility is often constrained by its capacity to bioaccumulate contaminants in anthropogenically stressed coastal environments. This study evaluates the proximate composition, macro-mineral profiles, and heavy metal concentrations of S. crassifolium flour harvested from Kaisomaru, Tomini Bay, to determine its safety and nutritional viability for industrial applications. Nutritional composition was analyzed using AOAC-standardized methods, while spectrophotometric techniques were employed to quantify essential minerals (Ca, Mg, Na, K, Fe) and toxic heavy metals (Cd and As). Results indicate that the seaweed is rich in dietary fiber and ash with low lipid content, confirming its status as a promising source of essential minerals, particularly calcium. However, the heavy metal assessment reveals a critical safety breach regarding arsenic (As) concentrations, which consistently exceed maximum residue limits established by the Indonesian National Standard (SNI 2690:2015). This bioaccumulation is driven by the structural "egg-box" configuration of the alginate-rich cell wall matrix, which facilitates the non-selective binding of both essential and toxic ions. Consequently, the study concludes that direct use of this raw biomass is restricted due to food safety risks. These findings establish that standardized post-harvest detoxification benchmarks, such as selective leaching or ionic pre-treatment, are mandatory to mitigate toxic metal burdens while preserving the nutritional integrity of the biomass, providing a necessary baseline for future functional food development.